REDESIGN OF CUSTOMS VALUE PROOF MECHANISM BY CUSTOMS ADMINISTRATION ACCORDING TO WTO PROVISIONS (DISPUTE STUDY AT TAX COURT) - Ardiyansah Ardiyansah (IBLAM Law Review)
Based on the analysis of the 2018 Tax Court decisions in customs value disputes, the judges' considerations in the decisions that reject customs decisions were mostly due to the appeal applicant is able to prove the correctness of the transaction value at trial based on supporting documents such as sales contracts, purchase orders, proof of payment, and bookkeeping. However, if there is any evidence that is incomplete or there is a different value, it is likely that the appeal is rejected. In order to explore how to prove customs value from normative and empirical aspects, research is compiled on the legal aspects of proving based on the provisions of WTO Agreemet on Implementation of Article VII of GATT . Normative juridical research result leads to one conclusion that the provisions for reversing the burden of proof are stipulated in the WTO Valuation Agreement, namely in article 17 and WTO Ministerial Decission 6.1. In addition, Technical Committee on Customs Valuation World Customs organization has published Case Study 13.1: “Application of Decision 6.1 of the Committee on Customs valuation”.